Proline bulky substituents consecutively act as steric hindrances and directing groups in a Michael/Conia-ene cascade reaction under synergistic catalysis - Putatunda, Salil; Alegre-Requena, Juan V; Meazza, Marta; Franc, Michael; Rohal'ová, Dominika; Vemuri, Pooja; Císařová, Ivana; Herrera, Raquel P; Rios, Ramon; Veselý, Jan (Chemical science, 2019)
In this study, we report a highly stereoselective and versatile synthesis of spiro pyrazolones, promising motifs that are being employed as pharmacophores. The new synthetic strategy merges organocatalysis and metal catalysis to create a synergistic catalysis using proline derivatives and Pd catalysts. This protocol is suitable for late-stage functionalization, which is very important in drug discovery. Additionally, a thorough computational study proved to be very useful to elucidate the function of the different catalysts along the reaction, showing a peculiar feature: the -CPh2OSiMe3 group of the proline catalyst switches its role during the reaction. In the initial Michael reaction, this group plays its commonly-assumed role of bulky blocking group, but the same group generates π-Pd interactions and acts as a directing group in the subsequent Pd-catalyzed Conia-ene reaction. This finding might be very relevant especially for processes with many steps, such as cascade reactions, in which functional groups are assumed to play the same role during all reaction steps.